CO-llaborative VI-rtual D-esign: A Collaborative Autoethnography on Conducting Exclusively Online, Data-Led Collaborations in the Creative Industries. (March 2022) - Spreadborough, Kristal; Cochrane, Thomas; Glasser, Solange; Sweeney, Damian; Harris, Julian; Belton, Amanda; Coleman, Kathryn; Melzack, Gene; Fitzgerald, Emily
This collaborative autoethnographic story of #DataCreativities articulates data traces found within the rapid move online in education and creative sectors in Melbourne, Australia. As a result of the lockdowns imposed to combat the initial spread of COVID-19, this collaboratory began within the anxieties of 2020. #DataCreativities takes a data-related approach to understanding the fast-paced shift to making, learning, teaching, and living in a crisis through research and art. Twelve months on, we figure (out) our own data and practice. We ask: What does CO-llaborative VI-rtual D-esign look like, how can it be established, and how can it be sustained?